Validity of measure of sitting time of IPAQ Questionnaire short version in undergraduate from Brazil - Franco, Dayana Chaves (2021)
The objectives of this study were to estimate the level of reproducibility of the sitting time measurements of the International Physical Activity Questionnaire (IPAQ-short version), and to analyze the concurrent validity of these measurements in relation the sedentary time measured by the accelerometer, in university students. A correlational study was carried out with a sample of 61 university students of a higher education institution from Minas Gerais, Brazil, who self-completed the IPAQ sitting time measurements, with interval of seven days for the purposes of the reproducibility analysis and used the accelerometer to estimate sedentary time and employment as the gold standard in the analysis of concurrent validity. The correlation analyzes via intraclass correlation coefficient (ICC) and Bland-Altman scatter plot were used to analyze the agreement. The significance level adopted was 5%. The average age was 21.54 years and 62.3% were female. The reproducibility of sitting time on a weekday was moderate (ICC = 0.51; p < 0.01), while on a weekend day it was low (ICC = 0.30; p = 0.01). The mean differences between sitting time using the IPAQ and sedentary time using the accelerometer on a weekday was -51 minutes and on a weekend was -64.7 minutes. Concluded that there were satisfactory correlations and agreements both in reproducibility and in comparison, with the criterion measure (accelerometer) of the sitting time measures measured by the IPAQ for application in university students.